Implikasi Implementasi Manajemen Mutu Jasa Terpadu dan Sertifikasi Guru dalam Peningkatan Mutu Layanan Pendidikan pada Sekolah Dasar di Kota Serang Provinsi Banten - Sudadio - (Jurnal Aplikasi Manajemen, 2012)
The success of organization very determined by the model and process management are applied, this is no exception on educational institutions, especially at the elementary school level has a central role and is very strategic for the success of the next higher education level. This study was used descriptive qualitative approach with a focus on the research problem is: ”Implications of Implementation of Integrated Service Quality Management and Quality Improvement of Teacher Certification in Education Services at Primary School in the City of Serang, Banten Province,” The instrument used in this study is the research using the guidelines of observation, interview, and documentation study guidelines, which aimed at the source data taken in clusters such as, cluster I to Primary Schools in the central city, cluster II Elementary School in the suburbs and cluster III Elementary School outside of town/away from downtown From the results of research and discussion, it can be stated that the implications of Total Quality Service and Total Quality management in improving the quality of services in primary school education in the city of Serang Banten Province, the implicacaions is good, indicated by the increase of the quality of services (achievement ) with an average of 77,25 in the year 2009 that in 2004 the mean is 70,26, meaning that with the approach of Total Quality Management and Total Quality Service and cetification of teachers can improve learning achievement of elementary school students with an average of 6,99 digits absolute numbers or there is an increase 0,099 percent.Keywords: Total Quality Service Elementary School